EMPIRICAL REVIEW OF BUSINESS CHALLENGES AND OPPORTUNITIES FROM THE COVID-19 PANDEMIC (Journal of Business Management and Accounting, 2022)
The SARS-CoV-2 coronavirus which causes the Covid-19 disease led to the most signiﬁcant change in the world order over the past century, destabilizing the world’s economy, businesses and communities, among others. Covid-19 has generated great uncertainty, and dramatically affected various industries, especially the service sector. This paper highlights the challenges and opportunities posed by the Covid-19 pandemic in terms of the role of businesses to ensure sustainability and safeguarding society. Based on empirical reviews, this study suggests that the pandemic has resulted in many business and economic challenges which include unemployment, low consumption of goods and services, financial distress, unethical business practices, mental distress, heavy business losses and business discontinuity. At the same time, the Covid-19 pandemic has created an opportunity for businesses in terms of enhance sustainability environment, enhanced voluntary CSR initiatives, shifting towards digital transformation and viable alternative business models. This study concludes that businesses must actively make use of opportunities to overcome or minimize the challenges of Covid-19.